ANALISA PENGARUH CURRENT RATIO, DEBT TO EQUITY, PRICE EARNING RATIO, NET PROFIT MARGIN, DAN TOTAL ASSET TURNOVER TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DIBURSA EFEK INDONESIA PERIODE TAHUN 2015-2021 - Levina Nathania; Jonny Siagian (Fundamental Management Journal, 2023)
Analisa Pengaruh Current Ratio, Debt to Equity, Price Earning Ratio, Net Profit Margin dan Total Asset Turnover Terhadap Return Saham Perusahaan Manufaktur yang Terdaftar di Bursa Efek Tahun 2015-2021 This research is to find whether CR, DER, PER, NPM and TATO have an effect on stock returns. Data were obtained using a purposive sampling method with criteria (1) Manufacturing companies in the industrial and chemical sectors listed on the Indonesia Stock Exchanged and consistent during the 2015-2021 study period (2) Number of manufacturing companies in the chemical, cement and ceramics industry sector listed on the Indonesia Stock Exchange years 2015-2021 (3). The results of the Current Ratio test have a significant effect on stock returns as indicated by the value of the test results t sign 0.010, the results is smaller than 0,05 (.010 < 0.05) so that means there is a positive and significant effect of current ratio on stocks returns. The results of the Debt to Equity Ratio test did not have a significant effect on returns marked the value of the test results t sign .0.00 which is smaller than (0.000 < 0.05), so that means there is negative effect and significant Debt to Equity on stocks returns. The results of the Price Earning Ratio do not have significant effects on stock returns marked by the value of the test results t sign 807 which is greater than 0.05 (.807 > 0.05), so that means there is not negative and significant effects on stock returns. The results of Net Profit Margin test have significant effects on stock returns marked by the value of the t test sign 042 which is less than 0.5 (0.042 < 0.05) , so it means that there is a positive and significant influence on stock returns. The results of the Total Asset Turnover test have a significant effect on stock returns marked by the value of the test results t sign .002 (0.002 < 0.05), so that means there is a positive and significant effect on stock returns. Keywords: Current ratio (CR), Debt to Equity ratio (DER), Price Earning Ratio (PER), Net Profit Margin (NPM), Total Asset Turnover (TATO).